2015
DOI: 10.5152/akd.2015.6156
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-modified albumin levels in patients with acute decompensated heart failure treated with dobutamine or levosimendan: IMA-HF study

Abstract: Objective:Ischemia-modified albumin (IMA) is a sensitive biomarker of myocardial ischemia. However, data on IMA levels in acute heart failure (HF) are still lacking. In this study, we aimed to evaluate serum IMA levels in acute decompensated HF and the effects of dobutamine and levosimendan treatments on IMA levels.Methods:This was a prospective, multicenter study that included 70 patients hospitalized with acute decompensated HF and left ventricular ejection fraction <35%. Blood samples for IMA measurements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Previous data on serum concentrations of IMA in patients with HF are limited. Dominguez-Rodriguez et al ( 8 ) showed that IMA levels are related to the left ventricular ejection fraction in patients with ST-segment elevation myocardial infarction treated with primary percutaneous coronary intervention and in those who developed acute HF IMA demonstrated a high sensitivity and negative predictive value for the diagnosis of HF In agreement with this previous study, Çavuşoğlu et al ( 7 ) showed that IMA is not only a promising biomarker for the diagnosis of acute HF but also useful for assessing the effect of inotropic therapy for acute HF.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Previous data on serum concentrations of IMA in patients with HF are limited. Dominguez-Rodriguez et al ( 8 ) showed that IMA levels are related to the left ventricular ejection fraction in patients with ST-segment elevation myocardial infarction treated with primary percutaneous coronary intervention and in those who developed acute HF IMA demonstrated a high sensitivity and negative predictive value for the diagnosis of HF In agreement with this previous study, Çavuşoğlu et al ( 7 ) showed that IMA is not only a promising biomarker for the diagnosis of acute HF but also useful for assessing the effect of inotropic therapy for acute HF.…”
supporting
confidence: 78%
“…In this issue, Çavuşoğlu et al ( 7 ) report the results of the first study to investigate IMA levels in patients with acute HF treated with dobutamine or levosimendan. They found that patients presenting with acute HF had elevated levels of IMA and also suggested that in-hospital acute HF therapy significantly reduced serum IMA levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] It has also been shown that serum endocan and IMA levels were significantly higher in infectious and other chronic diseases. [5][6][7] Balamir et al 1 did not mention whether acute or chronic infectious disease was an exclusion criterion in their study.…”
mentioning
confidence: 99%